OP0168 THE IMPACT OF RNA M6A METHYLATION ON INFLAMMATORY RESPONSES IN SALIVARY GLAND EPITHELIAL CELLS: INSIGHTS INTO SJÖGREN’S DISEASE PATHOGENESIS - Truffinet, F.; Arco Hierves, A.; Shalabi, H.; Pascaud, J.; Rivière, E.; Silva-Saffar, S. E; Fabbri, L.; Leboucher, S.; Besse, L.; Messaoudi, C.; Vagner, S.; Nocturne, G.; et al. (Annals of the rheumatic diseases, 2024)
Background:Sjögren’s disease (SjD) is an autoimmune condition marked by lymphocytic infiltration of exocrine glands, where salivary gland epithelial cells (SGECs) play a crucial role in initiating and amplifying inflammation. To address dysfunction, understanding the mechanisms behind pro-inflammatory signaling in SGECs is vital. Epitranscriptomics, a recent field, highlights RNA modifications’ impact on gene expression regulation. Writers such as METTL3/14 add methyl groups to RNA, while erasers like FTO remove them. Collectively, these modifications influence various aspects of RNA function.Objectives:To evaluate the expression of m6A machinery components in SGEC of controls and SjD. Additionally, we aim to define the mechanisms through which this newly identified post-transcriptional regulation controls inflammatory signal transduction in SGECs.Methods:We retrieved RNA-seq data from SGEC sorted from minor salivary gland biopsies of controls and SjD. We specifically looked at the expression of the m6A machinery by qPCR in sorted SGEC and by immunohistochemistry (IHC). Additionally, we determined the functional role of m6A writers in SGEC by performing knockdown experiments and by using pharmacological inhibitors. We assessed the expression of pro-inflammatory cytokines and chemokines, conducted transwell assays, and established SGEC/B cell co-cultures to comprehensively explore the impact of RNA m6A methylation on B cell survival and activation. Finally, we used immunofluorescence and flow cytometry techniques to detect the presence of dsRNA, and to explore their link with RNA methylation.Results:METTL14 showed increased expression in sorted SGECs from SjD subjects, and both METTL3 and METTL14 proteins increased in SGECs per IHC. Knockdown experiments targeting m6A writers demonstrated elevated CXCL10 and TNFSF13B expression upon SGEC activation by Poly(I:C) or IFNα, suggesting a protective effect of m6A against inflammation. Pharmacological inhibition of METTL3 increased CXCL10 expression, while inhibiting FTO decreased it, emphasizing RNA m6A’s role in modulating the inflammatory response. RNA-seq and pathway analysis upon METTL3 inhibition revealed interferon signature gene induction. Mechanistically, blocking METTL3 heightened the presence of dsRNA, as confirmed by immunofluorescence and flow cytometry. In parallel, inhibiting METTL3 not only increased the capacity of SGECs to attract immune cells in transwell assays, but also elevated the expression of CD38 on B cells in co-culture assays. Conversely, blocking FTO resulted in the opposite phenotype.Conclusion:Our findings highlight the role of RNA m6A pathway as a protector of SGECs in response to pro-inflammatory triggers. We hypothesize that the observed elevation of METTL3 and METTL14 in SGECs from SjD patients may not be sufficiently effective or significant in efficiently regulating the inflammatory response. Ongoing research is assessing the effectiveness of post-transcriptional regulation through the m6A pathway in preventing dsRNA accumulation in SGECs from SjD patients compared to controls.REFERENCES:NIL.Figure 1.A) RNA m6A methylation involves writers (METTL3/14), erasers (FTO, ALKBH5), and readers (YTH, IGF2BP families). B) SGECs, stimulated with Poly(I:C) (10 mg/mL), were treated with METTL3 inhibitor (STM2457), nonfunctional inhibitor (STM2120), or FTO inhibitor (FB23-2) to assess CXCL10 expression. C) Enrichment pathway analysis compared STM2457 and Poly(I:C)-treated SGECs vs. Poly(I:C)-treated SGECs. D) Transwell experiments studied SGECs pre-treated with STM2457, with or without Poly(I:C), in the lower compartment. PBMCs were added to the upper compartment. E) Coculture experiments where SGEC were preteated or not with STM2457 in the presence or not of Poly(I:C) and co-cultured with B cells.Acknowledgements:NIL.Disclosure of Interests:None declared.